Implications Of The Five Principles Of Love For The Land Perspective Of Shaykh Kholil Bangkalan On Security Psychology - Rifqi Muhammad; Gustina Gustina (Lembaga Pengembangan Kinerja Dosen, 2023)
With the anti-NKRI and anti-Pancasila movements, Indonesian society is agitated. This movement creates a feeling of insecurity in society. Sheikh Kholil Bangkalan has five principles of love for the homeland. This article aims to explore the implications of Sheikh Kholil Bangkalan's five principles of love for the homeland on security psychology. The implications can be seen through the cognitive, affective, psychomotor, and spiritual aspects. Then the scope of the implications for themselves, fathers, educators, children, students, families, neighbors, schools, communities, and the country Conclusion: First, the five principles of patriotism that are applied to oneself, family members, educators, students, and society will bring a sense of security. Second, to create a sense of security, the five principles of patriotism are given the meaning of cognitive, affective, psychomotor, and spiritual aspects. Third, create personal protectors and spreaders of security for individuals, families, neighbors, and communities, nationally and internationally, who have knowledge, feelings, attitudes, and spirituality about the five principles of love for the homeland. Fourth, security is actually a gift from Allah SWT to humans who defend their homeland with love and faith.